Morphology of Maxillary First Molars Analyzed by Cone-Beam Computed Tomography among Malaysian: Variations in the Number of Roots and Canals and the Incidence of Fusion - Aws Hashim Al-Kadhim; Zainul Ahmad Rajion; Normaliza AB Malik; Azlan Jaafar (Int Islamic Univ Malaysia, Kulliyyah Medicine, 2024)
Volume 16 Number 2, Dec 2017